The chronometry of single neuron activity: testing discrete and continuous models of information processing. - Mouret, Isabelle; Hasbroucq, Thierry (Journal of Experimental Psychology. Human Perception & Performance, 2000)
The authors propose to study information transmission by comparing the effects of experimental factors on reaction time (RT) with the latency of the changes in activity of single-neurons. An experiment was conducted in which a monkey (Macaca mulatta) performed a tactilo-manual 2-choice RT task and the compatibility of the stimulus-response mapping was manipulated. Task-related neurons were recorded in the monkey's primary somesthetic and motor cortices. The changes in activity of 105 of these neurons were classified either as sensory-like or as motor-like. The sensory-like changes occurred before the motor-like ones. The stimulus-response mapping exerted its entire effect on the RT after the sensory-like changes and before the motor-like ones. These findings suggest that the information was transmitted discretely from the processes affected by the mapping to the processes implemented by the motor-like changes. Reprinted by permission of the publisher.